The philosophy of religious phenomenon in social history - عباس ندى موسى (Al-Adab Journal, 2019)
Islamic History The philosophy of religious phenomenon in social history Throughout history, the religious phenomenon (religion and religiosity) has been a humanitarian need. It is natural that the religious phenomenon becomes an engine of history that has the same grave effect as other factors. History is not only driven by materialism, but also by spirituality, perception and imagination. History has long been a religious phenomenon of holiness and depth. Thus religion has been based on history, so that history has become an integral part of the general religious mind. The religious phenomenon also derived from its own characteristics, its general character, its religious discourse, its treatments, linguistic achievements and symbols. The great writer Al-Jahiz has dealt with many social issues and issues that he experienced, and because of his closeness to the strata of society in general and the close to them, especially the poor ones. The moral factors, such as adherence to religion and religiosity and adherence to values ​​and customs were factors of progress and high for the members of the Muslim community in his time, and their social status was higher than material factors such as wealth, property and income. For his part, Maskawi, the historian philosopher, emphasized the importance of focusing on the necessity of meeting people in periodic religious events such as prayer, pilgrimage, religious and non-religious occasions and festivals. Being an important source of commitment to love, laws, customs and traditions. Sufism emerged as a social phenomenon in the Abbasid era, despite its individuality, and spread among the members of Iraqi society in a collective manner, when the scope of corruption and chaos in all vital areas of the country, because of the wars that were almost ending to start again. Which left a lot of blood behind and left behind the psychological anxiety and moral decay, and the harsh life miserable, which left its effects on the members of the community in between, which was enough to create a social reaction, the people to resort to the religious phenomenon of asceticism and mysticism.